Perancangan Emergency Buttton Untuk Pendaki Gunung Dengan Sistem Komunikasi Multihop Berbasis LoRa - Gita Affrylia; Mohammad Fadhli; Lindawati Lindawati (Program Studi Teknik Elektro Universitas Khairun, 2021)
Mountain is one of the tourist destination that are currently in great demand by various circles of society, sepecially for young people. This is evidenced by the increase in mountaineering tourist visiotr data that increase every years. The increase in public interest in mountaineering also leads to many cases of accidents. That occur duirng mountaineering, such as the loss climbers in mountainousareas, the loss of climbers on muntain tracks, and other accidents that must immediately require emergency assistance. The difficult to find by guards and others search teams. Therefore, in this study wa designed an Emergency Button tool for mountaineers designed to be able to perform the emergency call process when a person has an accident while in an inaccessible terrain such as mountains. It is integrated in the LoRa-based Multihop Communications System an Global Positioning System (GPS). Signals or data sently by climbers through the emergency button in the form of coordinate points of the location of climbers. The coordinates sent by the climbers will later be sent to the mountain guard post server which was previously via Relay, the coordinate data has been received will automatically be uploaded to thinkspeak so that it can be acces using the internet and converted into a google maps display from. It is hoped that this will make it easier to find the location of climbers accurately and quackly.